PENGARUH INSTAGRAM TERHADAP MINAT BELI PRODUK UMKM OTAK-OTAK BAKAR - Prayogi, Adrian; Pancawati, Juwarin; Setiawan, Johan (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the influence of Instagram usage on consumer purchase intention for Otak-Otak Bakar products in Sepatan Timur District, using Otak-Otak Bakar Pak Slamet as the case study. A quantitative approach with a correlational survey method was applied, involving 100 respondents selected through convenience sampling. Data were collected using a Likert-scale questionnaire measuring four independent variables, namely Context, Communication, Collaboration, and Connection, toward Purchase Intention as the dependent variable. The data were analyzed using multiple linear regression. The results show that all four variables simultaneously have a significant effect on purchase intention. Partially, Communication, Collaboration, and Connection have significant influence, while Context shows no significant effect. Communication contributes through clear information and fast responses. Collaboration is the most dominant variable supported by consumer testimonials and reviews. Connection strengthens emotional closeness and digital loyalty, whereas Context does not strongly encourage purchasing decisions. These findings indicate that interaction, social proof, and emotional connection on Instagram play a stronger role in shaping purchase intention than visual content alone.